2014
DOI: 10.1007/s11103-014-0278-6
|View full text |Cite
|
Sign up to set email alerts
|

The wheat NHX antiporter gene TaNHX2 confers salt tolerance in transgenic alfalfa by increasing the retention capacity of intracellular potassium

Abstract: Previous studies have shown that TaNHX2 transgenic alfalfa (Medicago sativa L.) accumulated more K(+) and less Na(+) in leaves than did the wild-type plants. To investigate whether the increased K(+) accumulation in transgenic plants is attributed to TaNHX2 gene expression and whether the compartmentalization of Na(+) into vacuoles or the intracellular compartmentalization of potassium is the critical mechanism for TaNHX2-dependent salt tolerance in transgenic alfalfa, aerated hydroponic culture was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 40 publications
(57 reference statements)
1
32
0
1
Order By: Relevance
“…It has been shown that transgenics driven by constitutive promoters suffer from undesirable phenotypes, such as stunted growth and reduced yield (Wang et al, 2013). Proteins encoded by the DNA sequences of the NHX family members have been reported to be located on different cellular membranes (Zhang et al, 2015). For Na + transport across the membranes, proteins encoded by members of the NHX family genes utilize H + gradient as the driving force (Bassil et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that transgenics driven by constitutive promoters suffer from undesirable phenotypes, such as stunted growth and reduced yield (Wang et al, 2013). Proteins encoded by the DNA sequences of the NHX family members have been reported to be located on different cellular membranes (Zhang et al, 2015). For Na + transport across the membranes, proteins encoded by members of the NHX family genes utilize H + gradient as the driving force (Bassil et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Plants prevent accumulation of Na + in the cytosol to overcome Na + toxicity either by Na + efflux or compartmentalization of it into vacuoles through sodium-proton antiporters (NHXs) which belong to the cation/proton antiporter (CPA1) family of transporters (Mäser et al, 2001). Eight NHX genes have been reported in eukaryotic systems except in yeast (contains single NHX ) and in model plants like Arabidopsis and rice they have been characterized to some extent (Bassil et al, 2011a,b; Zhang et al, 2015). While Na + exclusion is carried out at the plasma membrane via salt overly sensitive (SOS) pathway (Zhang et al, 2001; Zhu, 2003), its sequestration is performed by NHX that is located at the tonoplast.…”
Section: Introductionmentioning
confidence: 99%
“…AtNHX1 overexpression mediated potassium transport and affected salinity response in tomato (Leidi et al, 2010). Transgenic alfalfa overexpressing the wheat NHX2 exhibited improved salt tolerance (Zhang et al, 2015). Furthermore, overexpression of alfalfa Rare Cold Inducible 2 ( RCI2 ) enhanced tolerance to salt stress in Arabidopsis (Long et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some drought-related genes can enhance the drought and salt tolerance of alfalfa. Expression of wheat NHX antiporter gene, TaNHX2 , in alfalfa resulted in an increase in salt tolerance [67,68]. Tang et al [69] increased both salt and drought tolerance of alfalfa by overexpressing Glycine soja WRKY20 , which was to enhance drought tolerance in Arabidopsis [70].…”
Section: Genetic Engineering For Improvement Of Alfalfamentioning
confidence: 99%